Salicylic acid treatment mitigates chilling injury in peach fruit by regulation of sucrose metabolism and soluble sugar content. (1st October 2021) - Zhao, Yaoyao; Song, Congcong; Brummell, David A.; Qi, Shuning; Lin, Qiong; Bi, Jinfeng; Duan, Yuquan
Highlights: A pre-storage treatment with salicylic acid reduced chilling injury in peach. Salicylic acid treatment regulated sugar metabolism and increased sucrose content. Treatment regulated the expression of genes related to sucrose metabolism. Treatment increased expression of two dehydration-responsive transcription factors. Abstract: Peach fruit stored in the cold are susceptible to chilling injury. A pre-storage treatment with the natural hormone salicylic acid can alleviate chilling damage, although the mechanism is unclear. We found that a treatment with 1 μmol L −1 salicylic acid for 15 min prior to storage at 4 °C delayed and reduced fruit internal browning, a symptom of chilling injury. Salicylic acid had a large effect on sugar metabolism, increasing total soluble sugars via a substantial increase in sucrose content. The transcript abundance of genes related to sucrose biosynthesis and degradation was significantly regulated by salicylic acid, consistent with the changes in sucrose content. Salicylic acid treatment also increased the expression of two DREB cold stress-related proteins, transcriptional activators that regulate cold resistance pathways. The results show that salicylic acid alleviates chilling injury in peach by multiple mechanisms, including an increased content of sucrose and activation of cold response genes.